Logics and system of urban actors in the governance of the operations for the precarious housing resorption in Algeria: Towards a participatory approach - Hichem Zitoune; Amira Manel Zouaoui; Meriem Chabou (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2020)
With the ambition of becoming a capital without slums, the city of Algiers has launched a veritable assault on the precarious habitat. However, since 2010, several demonstrations have broken out by the Slum-dwellers which testify to the failure in the governance of these operations. The obstruction of communication channels between local and central actors left the inhabitants with no choice but to provoke a riot. The objective of this work is to dissect the stages of implementation of these operations, through the analysis of governance and the system of urban actors set up by the Algerian government. We also carried out a study of the logics of urban actors in a precarious district in Algiers. This analysis allowed us to understand the social organization of the population, and the process of opinion-building in the face of the central policy of the State. Finally, as a hypothesis of our inductive approach, we sketched out a governance model for these operations in Algeria with a participatory approach, and responding to the issues identified during our research.